#TITLE_ALTERNATIVE# - HASAN FAUZIE (NIM : 12911010), MUHAMMAD
Identification of the front is done by analyzing the structure of vertical and horizontal temperature and salinity. Temperature and salinity data processing in cross section, having regard to the distribution of the horizontal temperature and salinity data for each layer depth is the essence of the process of identification of the front. The use of the T-S diagram is also one method that can be done to analyse the density of a distinction so that the density of waters that meet at a point referable occurrence of fronts. In accordance with its location, the pattern of currents in the waters of Raja Ampat is influenced by the mass of water from the Pacific Ocean to the West (Western Pacific Ocean) that move from the East to the West Sea and parallel to the northern part of the New Guinea mainland. Note that the currents in the waters of Raja Ampat is dominated by the influence of the wind, but for the Bay area and nearby small islands, the current pattern is more influenced by the tides. Average speed of the current in the waters of Raja Ampat is about 0.11 m/sec. Identification of front was done in the Raja Ampat Archipelago which has a geometric complex with the waters of the relief of the island Ã‚Â– a small island base, topography, and Strait--the narrow Strait. The waters of Raja Ampat is one of the main areas of investment cross-flows of Indonesia (Arlindo) that come from the Pacific Ocean. The presence in the waters of Raja Ampat arlindo certainly potentially bring together masses of warm water and cold water from the Pacific Ocean to the West and it also potentially gave rise to the occurrence of thermal fronts.